THE FORMATION OF SELF IDENTITY THROUGH MODELLING SCHOOL - Venturiny, Fernanda; Budi Lestari, Sri (Interaksi Online, 2017)
Self â€“identity is a component of the self-concept that allows the individual to maintain consistent stance and thereby enables one to occupy a stable position in his environment. The environment can be one of the supporting factors for a person in the search for identity, but also can be an inhibiting factor. This study aims to describe whether modelling school can help as a means of communication of its members and build a personal identity of women, with qualitative descriptive research methods and phenomenology approach. The theory used is the theory of fashion as communication that explains a person can communicate throught fashion. Because of fashion is one form of nonverbal communication. Then the theory of self-presentation that explains that this theory is an attempt to control someone elseâ€™s impression by arranging the behavior so that others interpret the identity as they wants. The results of the study showed that the interpersonal communication performed by the modelling school coach â€œHijabku Models Academyâ€ on the incorporated students was built throught the closeness gained from openness, attention, affection, and supportive attitude when communicating. This adjacency is used to build students self-confidence and expected to be able to establish student identities. Then, the belief of parents of children who are seeking self-identity throught modeling school become one of the driving factors for students to be more confident without feeling burdened, braver, and not easily shaken in building their own identity. Therefore, parents and trainers should continue to approach students who educate them by motivating them to be more confident and encourage them to open up for positive things, because parents and trainers have an important role in shaping attitudes and character of students who want to seek identity throught modeling school.